Insect Visitors of White Clover (Trifolium Repens L) and Their Relation With Environmental Variables in the Premises of Bhaktapur Multiple Campus, Nepal - Chaguthi, Gyanu; Dyola, Urmila (Journal of Institute of Science and Technology, 2018)
White clover plant, Trifolium repens L. one of the important forage crop, entirely depends on insects for its pollination. The research aims to study diversity and relative abundance of insect visitors of white clover and their relation with environmental variables in open ground of Bhaktapur Multiple Campus. Quadrate sampling method was used to explore diversity of insect visitors. Observations of the insects were conducted at morning (09:00 AM to 10:00 AM), noon (12:00 PM to 01:00 PM) and afternoon (3 PM to 4 PM) each day during study period. There were 3472 individuals of insect collected that belong to 20 species in three orders: Hymenoptera (69%), Lepidoptera (27%) and Diptera (4%). Number of individuals of visitors were comparatively higher at noon (1426) than in morning (1256) and lower in afternoon (790 individuals). Number of species found in morning and noon were same (20 species) whereas number of species found in evening was less (16 species). Apis cerana and Lampides boeticus are the most dominant species belonging to orders Hymenoptera and Lepidoptera respectively. The relation of diversity with environmental variables was correlated by using Multivariate analysis test. The test showed significant effect of light intensity, humidity, temperature and the latter one was the most influential factor on the composition of species. Journal of Institute of Science and Technology Volume 22, Issue 2, January 2018 Page: 86-91